Food Analysis Labwork Guide as A Learning Media - Sulistiyawati, Sulistiyawati; Cahya, Adi (Proceeding International Conference on Science and Engineering, 2017)
This study aimed to produce practical guide labwork using a project-based learning models to know the quality of products and to produce practical guide that can be used as a learning media. The study consisted of a preliminary study in the form of carbohydrat tests such as: iodine test, seliwanoff's test and moore test. Lipid solubility test within alcohol, ether and chloroform. Protein tests: biuret test, test and xanthoprotein ninhydrin test. Vitamin C tests: benedict test and iodine test. The results of the research were developed into a practical guide with coreldraw x6 software applications and Microsoft Word 2010 through the stages of data entry into the software developer, the preparation of layout and provision of the activity in laboratory. The final result of the product was a user-based food testing laboratory project. The product guide assess by a subject expert, a media expert, a biology teacher, 5 peer reviewers, while experts responded that module classified into "very good" with a percentage of 85.80%. The assessment from 20 students of class XI and XII High School get a percentage rating of 78.60% with good quality.